Local Rice Cultivars Grown On Tidal Swampland Near Coastal Area in South Kalimantan - Purnomo, Erry; Setiawan, Muhammad Lestio; Yuliani, Nurmili; Atmaja, Ery; Wahyuni, Muhammad; Saidy, Ahmad Rizali; Osaki, Mitsuru (UNIVERSITY OF LAMPUNG, 2008)
Local farmers in South Kalimantan (Banjarese farmers) use to grow local rice cultivars. The local rice growing areas are varied with distance from the coastal line. Consequently, the degree of salinity also varied. To overcome the salinity problem, farmers do their last transplanting earlier than the farmers in the inland area and grow the local rice cultivars that they believe tolerant to salinity. In this study, we investigate the local rice cultivars grown by the farmers in the coastal areas. Sixty paddocks were selected in Pulantan, Aluh-Aluh, Simpang Warga and Bunipah Villages, Aluh-Aluh District, Banjar Regency, South Kalimantan. The rice yield of each paddock was estimated by sampling 3 x 5 hills in 3 replicates. The soil was collected within the 3 x 5 hills area and analysed their electric conductivity (EC) and pH. We found that there were four families of local rice cultivars grown, namely, Palas, Bayar, Pandak and Siam families. Among all local rice cultivars grown, it was revealed that Pandak Putih and Siam Unus produced the highest yields. However, according to the farmers, Palas and Bayar families are the common rice tolerant to salinity. The good price of Siam family and good yield of Pandak family at other paddocks might become the considerant of growing such rice families in the study site.